Impact of Cardiac Interoception on the Self-Prioritization Effect - Honda, Tatsuru; Nakao, Takashi (Frontiers in Psychology, 2022)
Self-relevant information is processed faster and more accurately than non-self-relevant information. Such a bias is developed even for newly associated information with the self, which is also known as the self-prioritization effect (SPE). Interoception, which refers to the overall processing of information from within the body, is crucial for self-relevant processing; however, its role in SPE remains unexplored. In this study, we investigated the relationship between the magnitude of SPE and interoceptive accuracy (IAc), defined as one’s ability to accurately perceive one’s own interoceptive state. Additionally, to explore the causal relationship, we measured SPE by presenting self- or other-relevant stimuli based on the participant’s cardiac cycle in the shape-label matching task. We demonstrated that IAc was negatively correlated with the magnitude of SPE in terms of discrimination of the relevance of the stimuli. In addition, a correlation was observed only when the stimuli were presented during cardiac systole. Furthermore, IAc was negatively correlated with the processing of self-relevant stimuli but not with other-relevant stimuli. Collectively, our results show that individuals with higher IAc have relatively lower discriminative sensitivity to newly and temporary associated self-relevant stimuli presented during the accentuation of cardiac interoceptive information. Although SPE is a phenomenon in which newly self-associated stimuli are preferentially processed, our results suggest that individuals with higher IAc prioritized processing interoceptive information over temporarily associated self-relevant external information. Conversely, previous studies using paradigms other than the shape-label matching paradigm with familiar self-relevant stimuli, such as self-face, reported that interoceptive information enhances the processing of self-relevant stimuli. Whether interoceptive information enhances the processing of external self-relevant information may depend on the familiarity with the self-relevant stimuli and the experimental paradigm.